Evaluation of personality disorders in patients with Gender Identity Disorder (GID): An update - Azadeh M Meybodi; Atefeh G Jolfaei (Journal of Family Medicine and Primary Care, 2022)
Introduction: Gender dysphoria (GD) could cause various mental illnesses, but its main cause is unclear. GD patients also suffer from different personality disorders that increase the risk of side effects among them. The present review study is aimed to investigate the most recent studies on comorbid personality disorders in patients with GD. Materials and Methods: Online databases were searched using related keywords for collecting any related articles. After precise reviewing the abstract of all collected articles, those with more appropriate content were included in our study. Findings: The prevalence rate of personality disorders in GD patients has been reported to be from 15% to 80% by different studies. In line with the data from previous studies, it was revealed that borderline personality disorder is one of the most prevalent disorders among GD patients. Available comorbid personality disorders cause a wide range of side effects on the normal function of patients. Conclusion: The majority of studies carried out on the comorbidity of personality disorders have revealed that the possibility of personality disorders in GD patients is high. Anyway, further studies are required to understand the exact effect of psychological care on personality disorders in these patients.